Linkage of Customer Stewardship and Business Continuity in SME’s Post Pandemic using Marketing Mix 7P’s Analysis : Case Study of An Optical in Padang, Indonesia - Septrizarty, Rika; Kahar, Azmen; Angraini, Nadia; Asrilsyak, Sharnuke (Adabi : Journal of Public Administration and Business, 2023)
The current economic situation has not yet returned to stability as it was before  pandemic.  In fact. it  continues to decline. Ihsan Optical located  in Padang, West Sumatera, Indonesia has not yet recovered during  post pandemic. The sales post pandemic only 53% of pre pandemic. This research aimed to find out how the linkage of customer stewardship and business continuity of Ihsan Ooptical (a small and medium enterprise) can survive after Pandemic using marketing mix 7P’s analysis. Method of the research was qualitative research by conducting initial observation, in-depth interviews of  key informants: the owner,  employees and loyal customers.  Through tangible analysis, it was found that the costumers got the complacency from Product, Price, People and Process, whereas the other elements; Place, Promotion and Physical Evidence need to be improved. It was concluded even though there are shortcomings, costumers still feel satisfied. the value of customer stewardship behaviour applied by owner and employee are the thinking “in the customer’s shoes” and being a customer when serving  The quality assurance of products and services make  and create the business continuity.